2021
DOI: 10.1051/0004-6361/201936388
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of the aromatic and aliphatic carbonaceous nanograin features in the protoplanetary disk around HD 100546

Abstract: Context. Carbonaceous nanograins are present at the surface of protoplanetary disks around Herbig Ae/Be stars, where most of the ultraviolet energy from the central star is dissipated. Efficiently coupled to the gas, they are unavoidable to understand the physics and chemistry of these disks. Furthermore, nanograins are able to trace the outer flaring parts of the disk and possibly the gaps from which the larger grains are missing. However, their evolution through the disks, from internal to external regions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(116 reference statements)
0
5
1
Order By: Relevance
“…At 8.6 µm, the ratio appears to drop at small radii and increases from 0.75" (0.88 AU), but shows overall little change over 0"-1". These globally flat behaviors of the total emission/continuum ratios are different from what was observed by Habart et al (2021) in the HD 100546 disk. For HD 100546, the emission near the star is dominated by micronic grains, resulting in an important increase of the band-to-continuum ratios with distance to the star between 0" and 1", and constant ratios at larger distance.…”
Section: Aib Emission Versus the Continuumcontrasting
confidence: 85%
See 3 more Smart Citations
“…At 8.6 µm, the ratio appears to drop at small radii and increases from 0.75" (0.88 AU), but shows overall little change over 0"-1". These globally flat behaviors of the total emission/continuum ratios are different from what was observed by Habart et al (2021) in the HD 100546 disk. For HD 100546, the emission near the star is dominated by micronic grains, resulting in an important increase of the band-to-continuum ratios with distance to the star between 0" and 1", and constant ratios at larger distance.…”
Section: Aib Emission Versus the Continuumcontrasting
confidence: 85%
“…Overall, our data provides evidence of the domination of carbonaceous nano-grains in the infrared emission of the HD 169142 disk at all radii. This is to be linked with the presence of an inner cavity in the disk below 0.17" (20 AU), resulting in a lack of hot micronic grains, which were observed to dominate the continuum emission in, for instance, HD 100546 Habart et al (2021). account for the aromatic infrared bands and showed that the spectrum is intermediate between fully neutral, for which the 11.3 µm feature dominates over the 6.2, 8, and 8.6 µm features as well as the fully ionized interstellar PAH, showing predominant 6.2, 8, and 8.6 µm features over the 11.3 µm band (Peeters et al 2002).…”
Section: Aib Emission Versus the Continuummentioning
confidence: 99%
See 2 more Smart Citations
“…The larger component is a mixture of carbonaceous material and "astronomical silicate" (Draine & Lee 1984) with a mass ratio of C:Si=1:2, and a powerlaw grain size distribution f (a) ∼ a −3.5 (Mathis et al 1977), from a min = 10 µm to a max = 1000 µm. The mass ratio was set to this value because recent studies generally indicate that there is more silicate than carbon in protoplanetary disks (e.g., Habart et al 2021). The small silicate and larger dust were then mixed with a mass ratio of f small :(1f small ), where f small is a free parameter and represents the percentage of small grains in the mixture.…”
Section: Dust Compositionmentioning
confidence: 99%